The Dynamics of Self and Society In D. H. Lawrence’S the Rainbow: Exploring the Dynamics of Self and Society in D. H. Lawrence's The Rainbow (Journal of Advances and Scholarly Researches in Allied Education, 2014)
David Herbert Lawrence is moulded by the spirit of hisage. He is a man of strong individuality and egoism .He reacts sharply againstthe established conventions of the age. Therefore in his case, the primaryfacts that influence his works are his personal experiences and convictions,which at times corresponded with the tendencies of his age. Giving this belief The Rainbow explores the man-womanrelationship in all its aspects, creative as well as destructive. The totaldependence of the man on the woman, the dominance of the woman upon the man canhave tragic overtones.  Instead of aliberating effect the man-woman relationship can prove stultifying-a nullity.Marriage then could become an arena where the concerned parties are involved ina deadly conflict for supremacy. Lawrence believed that husband and wife shouldnot impose restrictions on each other. Rather, they should trust each other andsex should be a medium of emotional satisfaction. Intermingling of the dynamicsof self and society can be seen in The Rainbow which is the example of Lawrence’sgenius. In his essay “Of   Being andNon-Being” Lawrence outlines the central importance of the man-womanrelationship to the regenerative process: